Mechanism and control of Genipa americana seed germination - Ester Queiroz, Sue Ellen; Amaral da Silva, Edvaldo Aparecido [UNESP]; Davide, Antonio Claudio; Jose, Anderson Cleiton; Silva, Anderson Tadeu; Resende Fraiz, Ana Carla; Rocha Faria, Jose Marcio; Hilhorst, Henk W. M. (Wiley-Blackwell, 2012)
Genipa americana (Rubiaceae) is important for restoration of riparian forest in the Brazilian Cerrado. The objective was to characterize the mechanism and control of germination of G. americana to support uniform seedling production. Morphology and morphometrics of seeds, embryo and endosperm were assessed by light and scanning electron microscopy during germination. Imbibition and germination curves were generated and over the same time interval endosperm digestion and resistance were measured by puncture force analysis and activity assay of endo-beta-mannanase (EBM) in water and in abscisic acid (ABA). The gene encoding for EBM was partially cloned and its expression monitored by quantitative real-time-polymerase chain reaction. Embryos displayed growth prior to radicle protrusion. A two-phase increase in EBM activity coincided with the two stages of weakening of the micropylar endosperm. The second stage also coincided with growth of the embryo prior to radicle protrusion. Enzyme activity was initiated in the micropylar endosperm but spread to the lateral endosperm. ABA completely inhibited germination by inhibiting embryo growth, the second stage of weakening and expression of the EBM gene, but EBM activity was not significantly inhibited. This suggests that a specific isoform of the enzyme is involved in endosperm weakening. EBM may cause a general softening of micropylar endosperm cell walls, allowing the embryo to puncture the endosperm as the driving force of the decrease in puncture force.